2006
DOI: 10.3748/wjg.v12.i9.1352
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of human papilloma virus infection and its epidemiology in esophageal squamous cell carcinoma

Abstract: HPV infection is high in esophageal carcinoma of Henan emigrants, local residents and patients in Hubei Cancer Hospital.HPV is closely related with esophageal squamous cell carcinoma. HPV infection may play an important role in esophageal squamous cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Other Asian countries also have high rates of esophageal SCC, with an increasing incidence in Taiwan and Japan [4][5][6]. Tobacco use, alcohol consumption, drinking hot mate tea, chewing betel quid, and human papillomavirus infection have all been suggested to increase the risk of esophageal SCC, which is most common in males [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…Other Asian countries also have high rates of esophageal SCC, with an increasing incidence in Taiwan and Japan [4][5][6]. Tobacco use, alcohol consumption, drinking hot mate tea, chewing betel quid, and human papillomavirus infection have all been suggested to increase the risk of esophageal SCC, which is most common in males [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, other investigators have shown that HPV 16 infection has no significant effect on survival and does not improve survival after treatment (radiotherapy or chemotherapy) [24]. No correlation was found between HPV in esophageal squamous cell carcinoma tissues and in grade 1-3 esophageal squamous cell carcinoma cells [67]. In the study by Lyronis et al conducted at the University of Crete, no statistically significant correlation was found between the HPV status of the tumour samples and clinical parameters including gender, age of the patients, tobacco or alcohol use, differentiation grade of the lesions and stage of the disease [26].…”
Section: Hpv and Oesophageal Cancermentioning
confidence: 87%
“…In high-incidence areas of ESCC, other causal factors have been implicated, and there is increasing evidence that HPV 16 may be associated with ESCC in these high-risk areas. 7,18 In this study, we investigated the expression of p16 1NK4 and the possible role of high-risk strains of HPV in cases of ESCC in North American patients.…”
Section: Discussionmentioning
confidence: 99%